SELF-EFFICACY DAN SELF-REGULATED LEARNING PADA SANTRIWATI - Adhelia Rochmatika; Nur Eva; Farah Farida Tantiani (Psyche: Jurnal Psikologi, 2021)
ABSTRACTThis study aims to determine the relationship between self-efficacy and self-regulated learning on women students. This research is quantitative research and used simple regression statistical analytic method with a descriptive design. The population of this study was 128 women students. Data retrieval is done by simple random sampling technique. There were 83 students as research subjects. There are two instruments used in this study to collect data, the scale of self-efficacy has reliability of 0.979 and the self-regulated scale has reliability of 0.894. The results of this study show that (1) most women students have high self-efficacy, (2) most women students have high self-regulated learning (3) there is a significant effect between self-efficacy on self-regulated learning on women students (F = 35,654, R2 = 0.306, p <0.05). So self-efficacy gives an effect of 30.6% on self-regulated learning, while the remaining 69.4% is used by other variables that are not approved, such as, the social environment. The implication of this research is to maintain self-efficacy by increasing the strengths of women students in to solve self-regulated learning problems ABSTRAKPenelitian ini bertujuan untuk mengetahui (1) gambaran self-efficacy santriwati (2) gambaran self-regulated learning santriwati (3) gambaran pengaruh self-efficacy terhadap self-regulated learning pada santriwati. Penelitian ini menggunakan pendekatan kuantitatif dengan rancangan deskriptif dan analisis statistik regresi sederhana. Populasi penelitian ini berjumlah 128 santri, dan pengambilan data menggunakan teknik simple random sampling. Kemudian didapatkan 83 santri sebagai subjek penelitian. Terdapat dua instrumen pengumpulan data yang digunakan dalam penelitian ini yaitu (a) skala self-efficacy dengan reliabilitas 0.979 (b) skala self-regulated dengan reliabilitas 0.894. Hasil penelitian ini menunjukkan bahwa (1) sebagian besar santriwati memiliki self-efficacy tinggi, (2) sebagian besar santriwati memiliki self-regulated learning tinggi (3) ada pengaruh yang signifikan self-efficacy terhadap self-reulated learning pada santriwati (F = 35.654, R2 = 0.306, p < 0.05). Jadi self-efficacy memberikan pengaruh sebesar 30.6% terhadap self-regulated learning, sedangkan sisa 69.4% dipengaruhi oleh variabel lain yang tidak diteliti, seperti, lingkungan sosial. Implikasi dari penelitian ini adalah mempertahankan self-efficacy pada santriwati dengan mengoptimalkan kelebihan yang dimiliki santriwati dalam menyelesaikan berbagai persoalan self- regulated learning.